Transient performance study of an internally-cooled plate membrane liquid desiccant air dehumidification system. (November 2021) - Yang, Yu; Yan, Junwei; Zhou, Xuan; Xiao, Liehui; Huang, Si-Min
Highlights: An internally-cooled plate membrane liquid desiccant air dehumidification system has been applied. A dynamic model for the novel dehumidification system is built up. The transient performances of the system in a typical summer day are studied. The temperatures of the solution in the solution tanks vary rapidly after starting up. Increasing cooling water flow rate or reducing its temperature can improve the system performance. Abstract: An internally-cooled plate membrane liquid desiccant air dehumidification system has been adopted for air dehumidification due to its excellent ability of removing moisture. In this study, a dynamic model for the novel system is built up by coupling the model of each component. Based on the experimental data and the steady-state model, the dynamic model is validated to prove its accuracy. The transient performances of the system in a typical summer day are investigated. It is found that the operation process of the system during the daytime includes the start-up period and the stable running period. Owing to the rapid change of system parameters, the performances of the system during the start-up period are studied in detail. The results show that the temperatures of the solution in the solution tanks vary rapidly after starting up because of the low thermal inertia. Increasing cooling water flow rate or reducing cooling water temperature can improve the SDP of the system. The initial solution concentration and the volume of solution in the tank have a great effect on the start-up time, while the initial solution temperature has little influences.